2001
DOI: 10.1016/s0002-9440(10)64061-8
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Abnormalities Subdivide Ependymal Tumors into Clinically Relevant Groups

Abstract: Ependymoma occurs most frequently within the central nervous system of children and young adults. We determined relative chromosomal copy-number aberrations in 44 ependymomas using comparative genomic hybridization. The study included 24 intracranial and 20 spinal cord tumors from pediatric and adult patients. Frequent chromosomal aberrations in intracranial tumors were gain of 1q and losses on 6q, 9, and 13. Gain of 1q and loss on 9 were preferentially associated with histological grade 3 tumors. On the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
90
2
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 50 publications
13
90
2
4
Order By: Relevance
“…In addition, we provide evidence to support the proposal that classic (WHO grade 2) ependymomas from the region of the spinal cord are genetically distinct from intracranial classic (grade 2) and anaplastic (grade 3) tumours (Ebert et al, 1999;Hirose et al, 2001). …”
Section: Discussionsupporting
confidence: 82%
“…In addition, we provide evidence to support the proposal that classic (WHO grade 2) ependymomas from the region of the spinal cord are genetically distinct from intracranial classic (grade 2) and anaplastic (grade 3) tumours (Ebert et al, 1999;Hirose et al, 2001). …”
Section: Discussionsupporting
confidence: 82%
“…It is also possible that the number of deletions is underestimated by the FISH technique (eg, small deletions or relative RB deletions in an extensively polyploid tumor). However, our frequencies of 9p and 13q losses are similar to those previously reported using other techniques 11,14,24,[32][33][34] and there appears to be no clear suggestion of a prognostic association based on the available data thus far. Therefore, it is probable that genes other than p16 and RB may be targeted by the 9p and 13q deletions in ependymomas.…”
Section: Discussionsupporting
confidence: 83%
“…11,21,24,[31][32][33][34] Based on the recent finding of CGH detectable losses in high-grade examples, it was suggested that the RB pathway may be specifically targeted in the process of tumor progression. 24 In contrast, our larger study similarly identified a subset of ependymomas with 9p or 13q deletions by FISH, but there were no obvious associations with tumor grade, location, patients age, recurrences, or death. Given that relatively few recurrences and deaths occurred during the clinical follow-up period, it may be that a longer follow-up is necessary to exclude entirely associations with biologic behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 -13 It also has been suggested that pediatric ependymomas may behave more aggressively because of the immaturity of neural tissue in children 9,13 and that agerelated differences in outcome may be based on differences in cytogenetic aberration patterns between younger and older patients. 14 In addition, considerations regarding side effects and treatment tolerability are quite different for pediatric patients and adult patients. Thus, we believe that it is prudent to report results from adult and pediatric populations separately.…”
Section: Discussionmentioning
confidence: 99%